2014
DOI: 10.1021/ml400373j
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2,4-Diarylaminopyrimidine Analogues (DAAPalogues) Showing Potent c-Met/ALK Multikinase Inhibitory Activities

Abstract: By repurposing a typical dopamine D1/D5 receptor agonist motif, C1-substituted-N3-benzazepine or benzazecine, into the classical RTK inhibitor 2,4-diaminopyrimidine skeleton, a series of new 2,4-diarylaminopyrimidine analogues (DAAPalogues) were developed. Compounds 7 and 8a were identified possessing high potency against both c-Met and ALK kinases. Compound 8a displayed appreciable antitumor efficacy at the dose of 1 mg/kg in the ALK-driven BF3/EML4-ALK xenograft mice model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…We then evaluated the inhibitory effects of these compounds on the cell proliferation by using the protocol we previously reported. 47,48 As shown in Table 4, in the c-Met addicted NSCLC EBC-1 cells, seven compounds (12, 28a-d, 28f and 28h) outperformed the other counterparts with significant antiproliferative effects (IC 50 s less than 1 µM). However, these compounds suffered from a significant decrease in enzyme-tocell shift, likely due to their poor cellular penetration.…”
Section: Cell Proliferation Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We then evaluated the inhibitory effects of these compounds on the cell proliferation by using the protocol we previously reported. 47,48 As shown in Table 4, in the c-Met addicted NSCLC EBC-1 cells, seven compounds (12, 28a-d, 28f and 28h) outperformed the other counterparts with significant antiproliferative effects (IC 50 s less than 1 µM). However, these compounds suffered from a significant decrease in enzyme-tocell shift, likely due to their poor cellular penetration.…”
Section: Cell Proliferation Studymentioning
confidence: 99%
“…47,48 Compound 1 and panatinib were used as the reference compounds 28,31 for c-Met and VEGFR2 respectively. As shown in Fig.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In our effort to discover potent ALK inhibitors, [16][17][18] we came up with hybridized structures of LDK378 and CEP-37440, thereby leading to a novel structure, KRCAs, which is 2,4-diaminopyrimidine bearing 4-(isopropylsulfonyl)anilino and bicyclic benzazepine moiety as shown in Figure 2. Although Liu et al recently reported 2,4-diarylaminopyrimidine analog bearing bicyclic benzazepine moiety and methylacetamidoaniline as a c-Met/ALK multikinase inhibitor, [19] its chemical features differ from KRCAs. Herein, we report the synthesis of KRCAs and their anti-ALK activities in biochemical and cellular assays as well as PK and in vivo xenograft data of the selected compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was reported that ceritinib inhibited both ALK and IGF-1R, thereby showing better potency in in vivo study, compared to crizotinib. [19] Likewise, KRCA-0445 targeting both ALK and IGF-1R might give clinical benefits in the future development.…”
Section: Introductionmentioning
confidence: 99%